Aḥmad bin Muḥammad al-Marṣāfī’s Taqrīb fan al-luġa al-ʿarabiyya in the Context of the Reforms of the Arabic Grammatical Tradition during the Nahḍa - Ishankhanova, Muxlisabonu Turgunovna (The Lingua Spectrum, 2026)
This article presents a comprehensive examination of the true significance of the textbook Taqrīb fan al-luġa al-ʿarabiyya li-abnā’ al-madāris al-’ibtida’iyya by the Egyptian philologist Aḥmad al-Marṣāfī within the context of the Nahḍa educational reforms executed under Khedive Ismāʿīl and Minister ʿAlī Pasha Mubārak. The study thoroughly analyzes the complex adaptation of classical Arabic grammatical heritage (naḥw) to the practical needs of 19th-century primary mass education in Egypt. Particular attention is given to a detailed comparative analysis between the approaches of al-Marṣāfī and al-Ṭaḥṭāwī regarding the systematic organization of grammatical material, original definitions of fundamental syntactic categories (mubtada’, xabar, marfūʿāt, manṣūbāt), and functional topic placement. The author highlights al-Marṣāfī’s highly innovative techniques, such as modular structure, question-and-answer formats, visual tables, and practical contextual integration. The paper concludes that al-Marṣāfī’s work represents a pivotal milestone in the evolution of Arabic linguodidactics, successfully uniting classical academic rigor with modern school requirements.